2015
DOI: 10.1177/0394632015593220
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of intra-articular anti-tumor necrosis factor α agents compared to corticosteroids in a treat-to-target strategy in patients with inflammatory arthritis and monoarthritis flare

Abstract: The aim of this study was to assess safety and efficacy of ultrasonography (US)-guided intra-articular injections using tumor necrosis factor (TNF) blockers compared to corticosteroids in rheumatoid arthritis (RA) or psoriatic arthritis (PsA) patients, experiencing refractory monoarthritis despite the current systemic therapy. Eighty-two patients were randomized to receive three intra-articular injections monthly of either corticosteroid or TNF blockers. Primary endpoints were the safety and an improvement gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…[ 1 3 ] The deeper knowledge of pathophysiological mechanisms, the growing use of a treat-to-target management as well as the availability of powerful drugs strongly increased the percentage of patients achieving clinical remission and, consequently, reduced the percentage of those experiencing radiographic progression. [ 4 7 ] However, a significant proportion of patients may still develop associated complications and several studies demonstrated a close association between RA and cardiometabolic comorbidity. [ 8 10 ] To date, during RA, the leading cause of death are major cardiovascular events (CVEs); for this reason, growing research efforts are focusing on improving the management of these nonarticular outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 3 ] The deeper knowledge of pathophysiological mechanisms, the growing use of a treat-to-target management as well as the availability of powerful drugs strongly increased the percentage of patients achieving clinical remission and, consequently, reduced the percentage of those experiencing radiographic progression. [ 4 7 ] However, a significant proportion of patients may still develop associated complications and several studies demonstrated a close association between RA and cardiometabolic comorbidity. [ 8 10 ] To date, during RA, the leading cause of death are major cardiovascular events (CVEs); for this reason, growing research efforts are focusing on improving the management of these nonarticular outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…IA therapy with tumor necrosis factor inhibitors into large joints has shown some effectiveness, e.g. [ 57 , 58 ], even among patients who have failed IACI [ 59 ], and may be equivalent to if not superior than some forms of IA corticosteroids [ 60 – 62 ]. There is a single case report of 8 IA injections of infliximab administered to the TMJ over 36 weeks in an adult patient with psoriatic arthritis who had previously failed therapy with systemic infliximab as well as local IACI [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, studies in children with JIA have not been able to replicate this success [ 55 ]. The dose that can be administered into the TMJ of a child may be a limiting factor; the study by Carubbi et al (2016) demonstrated superiority of TNFi over CS only in large joints [ 62 ]. Additionally, the subject selection of JIA patients refractory to traditional and biologic DMARDs plus IA CS is one that is not ideal for the assessment of the effectiveness of IA infliximab.…”
Section: Methodsmentioning
confidence: 99%
“…During RA, the therapeutic strategies are aimed at preventing joint destruction by using synthetic disease modifying antirheumatic drugs (sDMARDs) as well as biologic agents [25]. In addition, a growing body of evidence is focused on the development of associated comorbidities and their management in rheumatic patients [68].…”
Section: Introductionmentioning
confidence: 99%